The effect of village fund management on infrastructure development in Tanjung Putus village, Pegajahan district, Serdang Begadai regency: English - Harahap, Rifqah; Sagala, Maduma Sari (SEAN Institute, 2024)
The purpose of this study was to determine the effect of Village Fund Management on infrastructure development in Tanjung Putus Village, Pegajahan Distric, Serdang Bedagai Regency. This research uses a quantitative method. The 220 residents of the Desa Tanjung Putus community make up the study's population, and the sample size in this study was 69 people. Random sampling is used in the determination process (random sample). The data sources for this research are primary data and secondary data. Primary data comes from observations, interviews, and questionnaires. Secondary data is obtained from data that has been documented. The analysis techniques used are simple linear regression analysis methods using the help of the SPSS version 22 program. The results of the research show that the Village Fund Management has a significant effect on infrastructure development in Tanjung Putus Village, Pegajahan District, Serdang Bedagai Regency, with a value of t-count > t-table that is (2.720 > 1.99601) and a significance value of 0.008 < 0.05. The coefficient of determination (R2) R-square was 0.548, or 54.8%, while the remaining 45.2% was influenced by other variables not discussed in this research.